A cultura amazônica em gêneros textuais: uma ferramenta metodológica para as aulas de língua portuguesa no contexto escolar - PEREIRA, Sebastiana Sarges (2023)
Textual genres are considered important tools when worked correctly in Portuguese language classes. In this way, the general objective of this article is to understand that the approach of Amazonian culture in textual genres is an important methodological tool to be worked on in Portuguese Language classes in the school context. It has as specific objectives: to approach the concept of textual genres and its exemplifications, in addition, to demonstrate the approaches that the documents that guide the curriculum in Brazil make in relation to textual genres; to know the aspects of Amazonian cultural identification through textual genres, in addition to identifying the cultural characteristics of the Amazon; to point out that the Amazonian culture linked to textual genres enables the teaching and learning process in Portuguese language classes. The methodological paths approach that the present research is considered: basic, exploratory, having qualitative approaches, being outlined by the bibliographic study. Thus, data collection was performed on Google Scholar, Scielo and public university repositories. The results point to discussions and reflections on the themes of textual genres and Amazonian culture. In this way, the textual genres linked to approaches to the Amazonian culture allow the student to learn significantly, as he will be studying its social practices, its culture, its geographic space and territory. It is concluded that regional literatures can be a great ally in the classroom, but it is up to the teacher to introduce them and work them correctly. 1